The relationship between euthanasia and terminal cases, incurable diseases, vegetative states, serious sequelar or intense irreversible suffering conditions and brain death (Saúde Ética & Justiça, 2009)
The authors address concepts concerning terminal state, euthanasia and orthothanasia as well as the relations between these concepts and the clinical conditions related to next-to-death situations, by pointing out and elucidating mistakes from the media and opinion makers. Resolution CFM 1805/2006 and the Medical Code of Ethics (Resolution CFM 1931/2009) are discussed from the point of view of the relations between their normative content and the above cited concepts.